Job Satisfaction And Organizational Commitment As Predictors Of Turnover Intention In Hospital Pharmacy Staff - yenny haryono; Pipit Festi (LP2IHKI UMSurabaya, 2025)
Objective: This study examines the determinants of turnover intention among pharmacy personnel in a private Type C hospital, addressing an underexplored human resource challenge that directly influences service continuity, medication safety, and health equity within hospital settings. Methods: Using a quantitative cross-sectional design, data were collected from all 30 employees of the Pharmacy Unit at XXX Hospital using a saturated sampling (total sampling) technique. Data were gathered through a structured and validated questionnaire based on a five-point Likert scale (1 = strongly disagree to 5 = strongly agree). The instrument measured job satisfaction (including satisfaction with work, salary, promotion, supervision, and coworkers), organizational commitment (including emotional attachment, support, and development opportunities), and turnover intention (including intention to leave, job search behavior, and thoughts of quitting), adapted from established theories and prior studies. Multiple linear regression using SPSS was employed to analyze the effects of job satisfaction and organizational commitment on turnover intention. Results: Job satisfaction shows a significant positive association with turnover intention (β = 1.084; p < 0.001), suggesting that external labor market pull factors may override job satisfaction in high-demand pharmacy professions. Conclusion: Strengthening organizational commitment, improving career pathways, and mitigating external job pressures are essential for sustaining pharmacy workforce stability in hospitals